2020
DOI: 10.1136/jnnp-2020-324254
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit changes in children with symptomatic spinal muscular atrophy treated with nusinersen

Abstract: ObjectivesTo elucidate the motor unit response to intrathecal nusinersen in children with symptomatic spinal muscular atrophy (SMA) using a novel motor unit number estimation technique.MethodsMScanFit MUNE studies were sequentially undertaken from the abductor pollicis brevis muscle after stimulation of the median nerve in a prospective cohort of symptomatic children with SMA, undergoing intrathecal treatment with nusinersen at a single neuromuscular centre from June 2017 to August 2019. Electrophysiological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 40 publications
4
58
5
Order By: Relevance
“…One prior study in children with later onset SMA treated with nusinersen, showed decreased MUNE and stable CMAP, but data in this study showed variability possibly reflecting the difficulty of electrophysiological assessments in children (14). Another recent study used the technique of MScanFit MUNE to investigate motor unit response in children undergoing nusinersen treatment and showed recovery of smaller motor units (28). This is in contrast to what we show here in that adults undergoing nusinersen demonstrated enlargement of average motor unit size (amplitude) without change in MUNE.…”
Section: Discussioncontrasting
confidence: 99%
“…One prior study in children with later onset SMA treated with nusinersen, showed decreased MUNE and stable CMAP, but data in this study showed variability possibly reflecting the difficulty of electrophysiological assessments in children (14). Another recent study used the technique of MScanFit MUNE to investigate motor unit response in children undergoing nusinersen treatment and showed recovery of smaller motor units (28). This is in contrast to what we show here in that adults undergoing nusinersen demonstrated enlargement of average motor unit size (amplitude) without change in MUNE.…”
Section: Discussioncontrasting
confidence: 99%
“…In a parallel study in non-ambulatory adults with SMA, we found a similar pattern of increases in CMAP and SMUP and stable MUNE ( 31 ). Interestingly, in a recent study that used MscanFit MUNE to estimate motor unit number in children with SMA treated with nusinersen, it was shown that nusinersen induced recovery of smaller motor units ( 32 ). Whether these differences are related to variability of biological response in children vs. adults or are explained by differences in technique requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 20 symptomatic SMA children (ages 4 months-16 years) undergoing nusinersen treatment, individuals with shorter disease durations showed greater increases in CMAP and MUNE, and these measures correlated with functional changes assessed by CHOP-INTEND and HFMSE. 123 In children with later-onset SMA (ages 2-15 years), CMAP and MUNE fluctuated slightly but were generally stable over 3 years of nusinersen treatment. 124 SMA type 2 children (n = 11, average age 15.4 months at diagnosis) showed progressive improvements in motor function and the majority demonstrated clinically meaningful improvements by the end of the study, while SMA type 3 children (n = 17, average age 43.6 months at diagnosis) showed only modest, and few clinically meaningful, functional improvements.…”
Section: Electrophysiology and Imaging Biomarkersmentioning
confidence: 95%
“…Disease progression, prognostic, predictive Kolb et al, 31 Kolb et al, 32 Arnold et al, 79 Swoboda et al, 114 David et al, 118 Weng et al, 119 Al-Zaidy et al, 122 Kariyawasam et al, 123 Darras et al 124 Motor unit number estimation (MUNE) Disease progression, prognostic, predictive Swoboda et al, 114 David et al, 118 Al-Zaidy et al, 122 Kariyawasam et al, 123 Darras et al 124 Motor unit number index (MUNIX) and motor unit size index (MUSIX)…”
Section: Physiologicmentioning
confidence: 99%